Geografia e arte na paisagem de Alexander Von Humboldt - Guido Lins Lopes Bragioni (2024)
Humboldt unleashes a series of influences on epistemology and scientific-geographical thought, and proposes a range of systematizations and discoveries that will substantiate and support his research and the structuring of science in posteriori. In this range of Humboldt's contributions, the art, the philosophy and the confluence of knowledge become fundamental to unveil and provide us the knowledge of the world and a theoretical review of contributions that permeated his scientific achievements. However, linked to art and philosophy, Humboldt's scientific project is often read in an outdated view or considered in a contradictory way. Moreover, this research is a resumption of reading Humboldt's works that seeks new identifications, which works with the philosophical and artistic approaches encountering with the field of geographic science. This research works in order to read Geography through the category of landscape in Humboldt, where we have, precisely, a great assemblage point for aesthetics, philosophy and science; and that bring to the scientific practice of our time new faces and delicacies that the production of knowledge needs to adhere to.